DINAMIKA LUASAN MANGROVE DI PESISIR PROBOLINGGO MENGGUNAKAN CITRA SATELIT - Tubagus Solihuddin; Aristiya Putri Widyantara (Indonesian National Institute of Aeronautics and Space (LAPAN), 2020)
Indonesia has the most extensive mangrove ecosystem in the world. One of mangrove ecosystem is located at Probolinggo coastal area, East Java Province. The mangrove area changes, over time whether it's decreasing or increasing. This research aims to calculate the extent of mangrove ecosystem in the past 20 years and map the distribution of mangrove in three different times i.e. 1998, 2008, and 2018. The satellite imageries used in this research are 1998’s Landsat 5 TM imagery, 2008’s Landsat 7 ETM+ imagery, and 2018’s Landsat 8 OLI imagery. Object-Based Image Analysis (OBIA) was employed to classify the mangrove and calculate the area for the 1998, 2008, and 2018 respective year. Normalized Difference Vegetation Index (NDVI) was used to determine the density level of mangrove canopy based on an object’s response to spectrum radiation red and NIR. The result shows that the mangrove area decreased from 1998 to 2008 constituting 514 Ha, and 386 Ha respectively. The mangrove area increased to about 464 Ha in 2018. The average mangrove canopy densities referring to NDVI analysis are 0.22012, 0.119492, and -0.019555 in respective years of 1998, 2008, and 2018. Within these 20 years, based on BAPLAN Forestry’s table classification of mangrove forest density, the mangrove forest densities at Probolinggo coastal area are relatively low.